Multilingualism & Translanguaging: A Review of Translanguaging Practices in the Linguistically Diverse Indonesian EFL Classrooms - Sutrisno, Dwi Budidarma (JOLLT Journal of Languages and Language Teaching, 2023)
This paper reviews the past decade of studies related to translanguaging practices on EFL learning context in Indonesia. This topic has crucially been discussed among scholars in educational settings due to the influence of multilingualism possessed by Indonesian EFL learners. The studies from 2010s-2020s are selected and critically reviewed by focusing on students‘ and teachers‘ perception of translanguaging practices used in EFL classrooms. The discussion covers meaningful insights from various education levels in Indonesia since the country is known as one of the most linguistically diverse communities. The analysis of the review shows how translanguaging contributes to helping the learning activities to be more comprehensive as well as develop students’ multilingual and linguistics competencies. Furthermore, it also lays out the use of code-mixing and code-switching are considered fundamental to balance the incorporation of three languages used while providing learning instructions and strategies. Finally, the pedagogical implication of translanguaging in a multilingual context is discussed. This paper hopes to encourage teachers to gain a deeper understanding of the language policies in the classroom and accommodate language development.